Enhancing Self Esteem of Orphan Teenagers through Self Discovery Training - Ema Zati Baroroh; Nindya Juwita Utimadini; Nabila Dafik Alhumairah; Ramadhanti Alifa Fatiah (Psympathic : Jurnal Ilmiah Psikologi, 2024)
This study aims to (1) determine the effect of self-discovery training and (2) provide a description of the changes in self-esteem after the intervention. The procedures were carried out using the quantitative pre-experimental method with a group pretest-posttest design. In this study, the sample population comprised 11 female teenagers aged 14 to 18 years, who were selected as participants using a simple random sampling method. The participants were residents of the Nur Fauzi Orphanage of Pontianak, West Kalimantan, Indonesia. Analysis using the Wilcoxon signed rank test showed that there were differences in self-esteem before and after the intervention. Qualitative assessment revealed that the participants experienced significant improvements. Meanwhile, qualitative assessment showed that the "Self-Discovery" intervention enabled the exploration of self-potential, indicating its effectiveness in enhancing self-esteem.